Analisis Pengaruh Kemudahan Penggunaan, Pengaruh Sosial Dan Risiko Terhadap Minat Penggunaan Financial Technology (Fintech) (Studi Kasus Pada Generasi Milenial Mahasiswa Universitas Dian Nusantara) - Damayanti, Silvani; Fathihani, Fathihani (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
This study aims to see the influence of the Ease of Use, Social Influence and Risk factors on the interest in transacting using financial technology in the millennial generation of Dian Nusantara University students. This research includes causal associative research and has independent and dependent variables. This type of research is a quantitative research. Where data collection techniques in the form of primary. The collection of data obtained is by means of a questionnaire. The sample in this study focused on the millennial generation of Dian Nusantara University students who used Fintech, namely 105 people. The analysis used is the SEM – PLS (Structural Equation Modeling – Partial Least Square) method with smartPLS software version 3.0.